Streptococcus mutans biofilm formation and cell viability on polymer-infiltrated ceramic and yttria-stabilized polycrystalline zirconium dioxide ceramic - Bottino, M. A. [UNESP]; Pereira, S. M.B. [UNESP]; Amaral, M.; Milhan, N. V.M. [UNESP]; Pereira, C. A. [UNESP]; Camargo, S. E.A.; Carvalho, A. B.G. [UNESP]; Melo, R. M. [UNESP] (Operative Dentistry, 2019)
Objective: The aim of this study was to investigate the biofilm formation and cell viability of a polymer-infiltrated ceramic (PIC) and an yttria-stabilized polycrystalline zirconium dioxide ceramic (Y-TZP). The null hypothesis was that there would be no difference in biofilm formation and cell viability between the materials. Methods and Materials: Streptococcus mutans biofilm was analyzed with scanning electron microscopy (SEM), confocal laser scanning microscopy, and colony counting (colony-forming units/mL). The cell viability (fibroblasts) of both materials was measured with 3-(4,5-dime-thylthiazol-2yl)-2,5-diphenyl tetrazolium) (MTT) test. Roughness measurements were also performed. Results: The PIC displayed higher roughness but showed similar colony-forming units and biovolume values to those of Y-TZP. SEM showed a higher amount of adhered fibroblasts on the PIC surface on the first day and similar amounts on both materials after seven days. Moreover, the materials were biocompatible with human fibroblasts. Conclusion: PIC and Y-TZP are biocompatible and present the same characteristics for biofilm formation; therefore, they are indicated for indirect restorations and implant abutments.